2016
DOI: 10.1371/journal.pone.0167583
|View full text |Cite
|
Sign up to set email alerts
|

A Modular and Affordable Time-Lapse Imaging and Incubation System Based on 3D-Printed Parts, a Smartphone, and Off-The-Shelf Electronics

Abstract: Time-lapse imaging is a powerful tool for studying cellular dynamics and cell behavior over long periods of time to acquire detailed functional information. However, commercially available time-lapse imaging systems are expensive and this has limited a broader implementation of this technique in low-resource environments. Further, the availability of time-lapse imaging systems often present workflow bottlenecks in well-funded institutions. To address these limitations we have designed a modular and affordable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Affordability and portability in fluorescence microscopy has been accomplished by retrofitting optical elements (objectives, filters, LEDS, lasers, lenses, mirrors) and 3D-printed parts to smartphones cameras [3,5,1113]. However, smartphones, although extremely powerful and unique, are difficult to reconfigure and take apart [14]; evolve at a rapid pace which may render them obsolete; constant software updates on the operating systems may disrupt their performance [15]; their size hampers further miniaturization and interferes in the integration with other additaments or sensors; and are not optimized for long-term biological experimentation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Affordability and portability in fluorescence microscopy has been accomplished by retrofitting optical elements (objectives, filters, LEDS, lasers, lenses, mirrors) and 3D-printed parts to smartphones cameras [3,5,1113]. However, smartphones, although extremely powerful and unique, are difficult to reconfigure and take apart [14]; evolve at a rapid pace which may render them obsolete; constant software updates on the operating systems may disrupt their performance [15]; their size hampers further miniaturization and interferes in the integration with other additaments or sensors; and are not optimized for long-term biological experimentation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Smartphone cameras use low‐cost CMOS technology, which are able to detect red, green and blue (RGB) light and therefore ideal for optical quantification in the visible wavelength range. An initial application of the integrated CMOS sensors in smartphones was to use them as external cameras for capturing images from the microscope ocular using 3D‐printed adapters . Furthermore, multiple studies have reported the design and development of attachments that are designed to comprise simplified optics that allow to perform microscopy observations directly .…”
Section: Smartphone‐based Imaging Technologiesmentioning
confidence: 99%
“…This animal possesses a decentralised neural network known as a 'nerve net' which is distributed across their spheroidal body, directly beneath the epithelial layer (Hernandez-Nicaise, 1973, Jager et al, 2011. Whole-mount immunofluorescence labelling of tyrosylated α-tubulin enables visualisation of their nervous system.…”
Section: Pleurobrachia Pileus Tissue Preparationmentioning
confidence: 99%
“…Whole-mount immunofluorescence labelling of tyrosylated α-tubulin enables visualisation of their nervous system. Tissue was processed in a manner similar to (Jager et al, 2011). Animals were fixed using 50% natural seawater and 50% paraformaldehyde (PFA, 8%) in phosphate buffered saline (PBS) (Thermo Scientific, 10209252) at room temperature.…”
Section: Pleurobrachia Pileus Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation